Comparison of fibre-optic-guided endotracheal intubation through a supraglottic airway device versus hyperangulated video laryngoscopy by emergency physicians: A randomised controlled study in cadavers. Issue 3 (May 2023) - Groombridge, Christopher J; Maini, Amit; Mathew, Joseph; Fritz, Peter; Kim, Yesul; Fitzgerald, Mark; Smit, De Villiers; O'Reilly, Gerard
Background: After failed endotracheal intubation, using direct laryngoscopy, rescued using a supraglottic airway device, the choice of subsequent method to secure a definitive airway is not clearly determined. Objective: The aim of this study was to compare the time to intubation using a fibre-optic airway scope, to guide an endotracheal tube through the supraglottic airway device, with a more conventional approach using a hyperangulated video laryngoscope. Methods: A single-centre randomised controlled trial was undertaken. The population studied were emergency physicians working in an adult major trauma centre. The intervention was intubation through a supraglottic airway device guided by a fibre-optic airway scope. The comparison was intubation using a hyperangulated video laryngoscope. The primary outcome was time to intubation. The trial was registered with ANZCTR.org.au (ACTRN12621000018819). Results: Four emergency physicians completed intubations using both of the two airway devices on four cadavers for a total of 32 experiments. The mean time to intubation was 14.0 s (95% confidence interval = 11.1–16.8) in the hyperangulated video laryngoscope group compared with 29.2 s (95% confidence interval = 20.7–37.7) in the fibre-optic airway scope group; a difference of 15.2 s (95% confidence interval = 8.7–21.7, p < 0.001). All intubations were completed within 2 min, and there were no equipment failures or evidence of airway trauma. Conclusion: Successful intubation of the trachea without airway trauma by emergency physicians in cadavers is achievable by either fibre-optic airway scope via a supraglottic airway device or hyperangulated video laryngoscope. Hyperangulated video laryngoscope was statistically but arguably not clinically significantly faster than fibre-optic airway scope via supraglottic airway device.